FAA AIRCRAFT CABIN AIR QUALITY STUDY (Tufts Archival Research Center, 2007)
Summary of a Federal Aviation Administration (FAA) study on aircraft cabin air quality outlining the parameters as directed by Congress. Includes National Academy of Science plans to study ten specific aspects of cabin air quality. Lists all aspects including the quantity and quality of fresh air per passenger, the adequacy of current preflight and in-flight health and safety instruction, a comparison of foreign industry practices, regulation and standards and an assessment of how the recommendations made in sections above relate to the health and safety of crew and passengers. Acknowledges that findings from this study can result in legislation regulating industry changes.